Developments in control theory towards glocal control - Qiu, Li, 1961-; Hara, Shinji, 1952- (Institution of Engineering and Technology, 2012)
Drawing upon a collection of research articles from celebrated authors in the field of control theory and its applications, this Festschrift honours the work of Professor Shinji Hara, and lays a solid foundation towards the 'glocal control' theory.
"This volume contains articles by the invited speakers for the symposium, "Developments in Control Theory towards Global Control", held in honor of (Shinji Hara) ... at the University of Tokyo on January 6-7, 2012"--Preface.
Keywords: Control theory -- Congresses.; Control theory -- Mathematical models -- Congresses.; elektronické knihy; electronic books